Students’ Mathematical Problem Solving Ability Based on The Steps of Ideal Problem Solving Viewed From Adversity Quotient (AQ) - Yuniara, Ridha; Saminan, Saminan; Abidin, Zainal; Johar, Rahmah (Al-Khawarizmi, 2023)
The ability of problem solving is one of essential mathematical abilities in learning mathematics. The facts in the field indicated that the problem solving ability of senior high school students were still low. Adversity Quotient (AQ) was presumed to play a role in the ability of students in solving problems. This research intended to describe the ability of students’ mathematical problem solving in accordance with the steps of IDEAL problem solving viewed from their AQ. The participants were consisted of three students of grade XI in one senior high school in Banda Aceh. The research finding indicates that the problem solving abilities of the students using steps of IDEAL problem solving regarding their AQ are differ. The climber solved problems by using all the steps of IDEAL problem solving, the camper only did four steps, and the quitter did not do any of the steps in solving the problem.